Do conditioning focused various-sided training games prepare elite youth male soccer players for the demands of competition? - G. Sydney, Michael; Wollin, Martin; W. Chapman, Dale; Ball, Nick; K. Mara, Jocelyn (Biology of Sport, 2022)
Relative metrics (i.e. distance covered per minute of match time) are regularly used to quantify soccer player movement demands. However, limited literature is available concerning the peak player demands during training. This study aimed to compare the relative and peak demands of conditioning-focused varioussided training games (VSG) to competition matches in elite youth male soccer players according to playing position. Data from twenty-nine competition matches (national) and twenty-two VSGs (small, medium, and large) were collected for twenty-three elite under-17 soccer players using 15-Hz portable global positioning system tracking devices (GPSports, Canberra, Australia). Relative player movements were reported as total distance (TD) and high-speed running distance (HSRD) (> 5.0 m/s) per minute of total playing time. Peak player movements were calculated using a 1-minute rolling epoch length, reported as the maximum TD and HSRD. Linear mixed models demonstrated interactions between VSG type and player position for relative TD (p < 0.001) and HSRD (p < 0.001), and peak TD (p = 0.010) and HSRD (p = 0.003). The relative TD of VSGs were greater than match-play for all player positions. However, only Central Defenders demonstrated similar HSRD in MSGs and LSGs compared to match-play when analysed using relative calculations. External Attackers also replicated match-play relative HSRD demands in LSGs. No VSG type was found to replicate or supersede the peak player movements of match-play across any playing position. Consequently, VSGs should be supplemented with highspeed running training to prepare players for the peak running requirements of match-play.